Perceived image of Chinese tourists on Malacca world heritage sites - Liew, Jan Fui (2015)
Understanding of a destinations image is essentially important for destinations that wish to influence traveller’s decision–making and choice. The perceived image is unique based on travellers own memories, associations or imaginations of a destination. As emphasized by numerous researcher that the tourist image is the factor that influence tourist behaviour. The purposes of this study were to identify the characteristic of the Chinese tourists and the attributes perceived image by this tourist group. Moreover, the study attempts to evaluate the overall perceived image of the Chinese tourists. The study area is Malacca World Heritage Sites. The questionnaire survey was conducted at three different sites in Malacca. The sample population for this study was composed of the Chinese tourists who visited Malacca World Heritage Sites. In this study, descriptive analysis method is used to analyse the data collected. The result reveals that Malacca is an attractive destination for Chinese tourists, with strengths in most of the important attributes, such as a great variety of heritage building, plentiful historical sites and unique architecture and townscape. Nevertheless, those who visit Malacca are likely to find Malacca not a good opportunity for wildlife observation. Moreover, in the point of view of Chinese tourists Malacca is not a place with good bargain and shopping heaven as well. The findings reflected the perceived image of Chinese tourists; consequently, it could contribute to the future tourism practitioners who aim to promote Malacca among the Chinese tourists to be a desirable international tourism destination.